The impact of IFRS 9 on the cyclicality of loan loss provisions - Smilla Hansen; Michel Charifzadeh; Tim A. Herberger (Journal of Corporate Accounting & Finance, 2023)
Through their procyclical behavior, loan loss provisions have been determined as one of the factors that contribute to financial instability during a crisis. IFRS 9 was introduced in 2018 with an expected credit loss model replacing the incurred loss model of IAS 39 to mitigate the effect in the future. Our study aims to analyze loan loss provisions of major banks in the Eurozone to determine for the first time if the implementation of IFRS 9, as intended by regulators, has a dampening effect on procyclicality, especially during the stressed situation under COVID-19. We analyze 51 banks from 12 countries of the European Monetary Union using 2856 firm-year observations. While no robust evidence of less procyclicality can be found after the implementation of IFRS 9 until the pandemic, we find evidence that loan loss provisions moved countercyclical during 2020, indicating an alleviating effect at the beginning of the exogenous shock.
Keywords: 650; eurozone; expected credit loss model; IFRS; loan loss provisions; procyclical effect